Antioxidant properties of stingless bee honey and its effect on the viability of lymphoblastoid cell line - Hazirah H,; Yasmin Anum MY,; Norwahidah Abdul Karim, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Research on the medical benefit of stingless bee honey (kelulut honey) is rather new although it has been used as traditional food and additive for ages. The primary objective of our study was to evaluate the antioxidant properties of kelulut honey and its effect on lymphoblastoid cell line. We analysed the antioxidant properties of kelulut honey by ferric reducing antioxidant potential assay, total phenolic and flavonoid contents using UV spectrophotometry. The total phenolic content, total flavonoid content and ferric reducing antioxidant potential of Malaysian kelulut honey produced by Trigona spp. were found to be 844.45 mg RE/kg honey, 78.29 mg RE/kg honey and 1132.66 mM FE/kg honey, respectively. Our findings showed a strong correlation between total phenolics and flavanoids contents with its antioxidant potential at R2 = 0.920 and R2 = 0.951, respectively. The effect of honey on cell viability of lymphoblastoid cell line (LCL) was also investigated. The cells were cultured in RPMI-1640 medium supplemented with 0 - 500 μg/mL of kelulut honey for 24 hours. Cell viability was quantitated using 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium, MTS assay showed that honey supplementation boosted the viability of LCL up to 164.64% (p< 0.01). The significant increase in cell viability might be modulated by the antioxidant properties of kelulut honey.